Public enemy number two - Horowitz, Anthony, 1955- (Walker Books, 2007)
Framed for a jewel robbery, quick-thinking thirteen-year-old Nick Diamond finds himself sharing a prison cell with Johnny Powers, juvenile delinquent and Public Enemy Number One. Suddenly, Nick is Public Enemy Number Two! His only chance at breaking out of jail is his older—and much dimmer—brother Tim. He's possibly the world's worst private detective, but Nick has no choice. Can Nick break out of jail, defeat Ma Powers and her gang, recover a stolen vase from an underwater hideout, and defuse a ticking time-bomb all while keeping his older brother from wrecking everything?